Recent Advances in Probiotics as Live Biotherapeutics Against Gastrointestinal Diseases - Kota, Rohini K.; Ambati, Ranga Rao; Y.V.V., Aswani Kumar; Srirama, Krupanidhi; Reddy, Prakash Narayana (Current Pharmaceutical Design, 2018)
Background: Gastrointestinal (GI) diseases are a major cause of emergency department visits requiring hospitalizations leading to considerable burden on global economy. Several factors contribute to the onset of gastrointestinal diseases such as pathogens (parasites, bacteria, virus, toxins etc.), autoimmune disorders and severe inflammation of intestine. Objective: One common feature among all these diseases is the dysentery and alteration of gut microbiota composition (gut dysbiosis). Apart from conventional therapies such as antibiotics and ORS supplementation, gut microbiota modulation with probiotic supplementation has emerged as a successful and healthy alternative in mitigating GI diseases. In this review our goal is to discuss the causes of gastrointestinal diseases and the present state of various therapeutic strategies such as probiotics as live biotherapeutics and Fecal Microbial Transplants (FMT's). Conclusion: Several reports and clinical trials point out to the beneficial effects of probiotics in modulating the gut microbiota and improving the side effects of gastrointestinal diseases. Live biotherapeutics and FMT’s could be suitable and successful alternatives to conventional therapies in mitigating the gastrointestinal pathogens.
Keywords: therapy